The changing gender disparity in Malaysian higher education: Where are the boys? - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2012)
Participation in higher education has traditionally been dominated by males, but over the past decades, gender differentials in higher education have narrowed and reversed in favour of the females. In Malaysia, females now outnumber males in higher education institutions (HEIs) and in most fields of study. This paper seeks to illustrate the extent of the gender gap in Malaysian higher education across different HEIs, levels of study and fields of study. More importantly, this paper argues the need of understanding the underrepresentation of boys, the challenges that impede their transition from secondary to higher education and highlight the possible implications due to gender imbalance and a lack of an understanding of the boys.